(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The large-scale reforms carried out in our country are aimed at achieving the ambitious development goals of Uzbekistan, which have no equal in the world. The special attention paid to the education of our youth can be seen from the Presidential schools, the School of Creativity, educational organizations based on public-private partnerships, and finally, the reforms that are being implemented in the way of the organization and operation of non-governmental educational organizations. The reforms carried out by our state and government are aimed not only at pre-school and general high school education, but also in the direction of opening branches of private higher education institutions and prestigious higher education institutions of developed foreign countries, which will enable the formation of a healthy competitive environment in the higher education system, and the establishment of joint educational programs with them, is appearing. The types of activities related to the social sphere carried out in our country, in particular, the benefits created for legal entities engaged in the provision of non-state educational services, the correct organization of their tax relations as a legal entity, current tax benefits and their relative classification, conditions and procedures for using benefits, benefits In our opinion, the formation of skills in the correct use of the accounting reporting procedure and the current regulatory and legal documents related to this field is one of the most urgent issues today. Some of the provided benefits have their own characteristics in terms of duration, and some in relation to the type of activity. In this process, the correct use of tax benefits, their correct reflection in accounting is important, of course.